2013
DOI: 10.1089/ten.tea.2012.0674
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factors Polymerized Within Fibrin Hydrogel Promote Amylase Production in Parotid Cells

Abstract: Salivary gland cell differentiation has been a recurring challenge for researchers as primary salivary cells show a loss of phenotype in culture. Particularly, parotid cells show a marked decrease in amylase expression, the loss of tight junction organization and proper cell function. Previously, Matrigel has been used successfully as an extracellular matrix; however, it is not practical for in vivo applications as it is tumorigenic. An alternative method could rely on the use of fibrin hydrogel (FH), which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 58 publications
3
45
0
Order By: Relevance
“…In contrast to threedimensional (3D) studies performed with fibrin 22 and hyaluronic acid, 20,23,25 PEG is a bio-inert material 26 that can be modified to provide specific biological cues in a novel ''bottom up'' approach to tissue engineering. Numerous ECM proteins that are important to salivary gland development and differentiation have been identified, 106 and some of these such as laminin-111 21 and perlecan 23 have been incorporated into biomaterials.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to threedimensional (3D) studies performed with fibrin 22 and hyaluronic acid, 20,23,25 PEG is a bio-inert material 26 that can be modified to provide specific biological cues in a novel ''bottom up'' approach to tissue engineering. Numerous ECM proteins that are important to salivary gland development and differentiation have been identified, 106 and some of these such as laminin-111 21 and perlecan 23 have been incorporated into biomaterials.…”
Section: Figmentioning
confidence: 99%
“…Numerous studies have focused on feasibility of using nanofibers or hydrogel-based scaffolds. [15][16][17][18][19][20][21][22][23][24][25] Although a few studies have translated their findings in vivo, 16,17,23 no study to date has demonstrated that the tissue developed on or within biomaterials contributes to restoration of gland function. To overcome these limitations, we propose use of poly(ethylene glycol) (PEG) hydrogels for salivary gland cell transplantation.…”
mentioning
confidence: 99%
“…Western blot analyses were performed as described previously (McCall et al, 2013) and detailed in the Appendix Methods.…”
Section: Western Blot Analysesmentioning
confidence: 99%
“…Unfortunately, matrigel cannot be used for in vivo applications as it is derived from a mouse sarcoma cell line [66] and several studies have found it to be tumorigenic [67][68][69]. Culturing cells on fibrin hydrogels has been investigated, but it has failed to produce the same three dimensional morphology [67].…”
Section: Bioengineered Glandsmentioning
confidence: 99%
“…Culturing cells on fibrin hydrogels has been investigated, but it has failed to produce the same three dimensional morphology [67]. As an alternative technique, one group has developed precisely constructed craters lined with poly-lactic-co-glycolic acid (PLGA) nanofibers to mimic a basement membrane.…”
Section: Bioengineered Glandsmentioning
confidence: 99%